Quantum batteries: Unlocking the future of high-tech energy storage - Khadim, Bazgha; Majid, Abdul; Belgibayeva, Ayaulym; Jin, Yongcheng; Bulut, Niyazi; Alkhedher, Mohammad (Elsevier, 2026)
The evolution of quantum batteries (QBs) lies at the core of the studies connected to the high-tech energy storage technologies. The non-traditional quantum systems make use of the entanglement and the coherence alongside the out-of-equilibrium to achieve the improvements in the charging rate, scaling of the energy capacity and size. This review provides insight into how QB models have evolved since their simple theoretical frameworks such as Dicke and Tavis-Cummings models to highly sophisticated structures of spin-chain structure, open/closed quantum system and random models. It has been discussed on the specialized properties of QBs that make them capable of super extensive charging and dark state-based energy storage robustness as well as comprehensive mathematical descriptions of these theoretical models. In this research, advances in QB technology, via research of superconducting circuits coupled with NV centers and molecular photonic systems that had reached room temperature operation are covered. Individual Hamiltonians Analysis has been done to determine how extractable work and charging speed are sensitive to system size and control field parameters and the strength of the coupling. Experimental research leads to the development of QB technologies using superconducting qubits, photonic micro cavities, spin-based systems and produces recent operational success using realistic parameters beyond low temperatures up to room temperature.
Keywords: Quantum batteries; Coherence; Qubits; Dark state